Coal liquefaction pitch mixture and method for producing the same

CN121085579BActive Publication Date: 2026-10-27RES INST OF HIGHWAY MINIST OF TRANSPORT +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511325543.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2026-10-27
Estimated Expiration
2045-09-17

AI Technical Summary

Technical Problem

现有的煤液化沥青混合料,存在导致高温抗车辙性和低温抗裂性差以及不耐久的问题

Benefits of technology

本发明制备的煤液化沥青混合料包括集料、矿粉、基质沥青、煤直接液化残渣、增韧回收聚乙烯、丙烯酰胺活化胶粉接枝SBS、高岭土改性氧化石墨烯和硅烷偶联剂。其中,煤直接液化残渣和高岭土改性氧化石墨烯构成了强大的刚性纳米骨架,提高了煤液化沥青混合料高温下抵抗塑性变形的能力。增韧回收聚乙烯和丙烯酰胺活化胶粉接枝SBS形成了互穿聚合物网络,提供了巨大的弹性恢复能力和柔韧性,抵消了煤直接液化残渣的脆性,使混合料在低温下不易开裂。硅烷偶联剂增强了集料-沥青界面强度,在集料和沥青之间形成了化学键合的牢固界面,提高了抗水损害能力与耐久性。本发明提供的煤液化沥青混合料将煤化工固废、废旧塑料和废旧轮胎转化为高性能路面材料,实现了高附加值的资源化利用,适用于极重交通、高温地区、长大纵坡及机场跑道等极端苛刻的场合。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses coal liquefaction asphalt mixture and a preparation method thereof, and relates to the technical field of asphalt materials.The coal liquefaction asphalt mixture comprises the following raw materials in mass parts: coarse aggregate 50-60 mass parts; fine aggregate 30-40 mass parts; mineral powder 4-8 mass parts; base asphalt 2-3.5 mass parts; coal direct liquefaction residue 1.5-3 mass parts; toughened recycled polyethylene 0.3-0.8 mass parts; acrylamide activated glue powder grafted SBS 0.5-1.5 mass parts; kaolin modified graphene oxide 0.05-0.15 mass parts; and silane coupling agent 0.2-0.4 mass parts.The coal liquefaction asphalt mixture prepared by the application has ultrahigh modulus and excellent toughness, and exhibits excellent low-temperature crack resistance, high-temperature rut resistance and water stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of asphalt materials technology, specifically to a coal liquefaction asphalt mixture and its preparation method. Background Technology

[0002] The main characteristics of my country's energy structure are "abundant coal, scarce oil, and limited gas." Coal dominates primary energy supply, accounting for as much as 67.5%. Due to the limitation of energy resources, coal has always occupied a major position in the energy production and consumption structure. Coal liquefaction technology is one of the most influential technologies for achieving the clean and efficient utilization of coal. There are two methods: direct coal liquefaction and indirect coal liquefaction, both of which produce liquefaction residues. These residues are rich in various organic compounds as well as oxides of metals and non-metals, and have high utilization value.

[0003] In modern road engineering, especially in projects involving heavy loads and humid, hot environments, the selection and performance of asphalt pavement materials are crucial. As road construction demands increasingly higher levels of durability, load-bearing capacity, and environmental adaptability, traditional asphalt concrete is gradually revealing problems such as aging, cracking, and rutting. These problems not only reduce the service life of the pavement but also lead to high maintenance costs. Currently, mainstream technologies often employ hard asphalt, high-proportion polymer modifiers, or fiber admixtures. Coal liquefaction residue, as a byproduct of coal chemical processes, is characterized by high aromatic content and high hardness, making it a potential material for improving the modulus of asphalt mixtures. Existing technologies typically involve simply processing coal liquefaction residue into granules or preparing modified particles through physical blending with SBS, SBR, rubber powder, etc., before mixing it with base asphalt in a certain proportion. However, this approach has the following inherent drawbacks: physical blending makes it difficult to achieve molecular-level fusion of coal liquefaction residues with polymer modifiers and matrix asphalt, resulting in poor compatibility, easy phase separation, and unstable long-term performance; the improvement in the modulus of the binder mainly depends on the hardness of the coal tar pitch itself, with limited improvement in high-temperature performance. Therefore, existing coal liquefaction asphalt mixtures suffer from poor high-temperature rutting resistance, poor low-temperature crack resistance, and lack of durability, which severely limits the application of this technology. Summary of the Invention

[0004] The purpose of this invention is to provide a coal liquefaction asphalt mixture and its preparation method, thereby solving the following technical problems: Existing coal liquefaction asphalt mixtures suffer from poor high-temperature rutting resistance, low-temperature crack resistance, and lack of durability.

[0005] The objective of this invention can be achieved through the following technical solutions: A coal liquefaction bitumen mixture comprises at least the following raw materials in parts by weight: 50-60 parts by weight of coarse aggregate; 30-40 parts by weight of fine aggregate; 4-8 parts by weight of mineral powder; 2-3.5 parts by weight of matrix asphalt; 1.5-3 parts by weight of coal direct liquefaction residue; 0.3-0.8 parts by weight of toughened recycled polyethylene; 0.5-1.5 parts by weight of acrylamide activated rubber powder grafted with SBS; 0.05-0.15 parts by weight of kaolin-modified graphene oxide; 0.2-0.4 parts by weight of silane coupling agent.

[0006] As a further aspect of the present invention: the oil-aggregate ratio of the coal liquefaction pitch mixture is 4.5%-5%, the coarse aggregate, the fine aggregate and the mineral powder are selected from AC-13 type or EME-20 type gradation, and the particle size of the coal direct liquefaction residue is 0.1-1mm.

[0007] As a further aspect of the present invention, the preparation method of the acrylamide-activated adhesive powder grafted with SBS includes the following steps: The adhesive powder was soaked and stirred in sodium hydroxide solution, washed and dried to obtain alkaline-washed adhesive powder. The alkaline-washed adhesive powder, potassium persulfate, and acrylamide were added to deionized water, stirred, washed, filtered, and dried to obtain acrylamide-activated adhesive powder. The acrylamide-activated rubber powder, maleic anhydride, and SBS were added to cyclohexane, and the reaction was carried out under high temperature and nitrogen atmosphere with the initiator benzoyl peroxide. The mixture was then distilled under reduced pressure and dried to obtain acrylamide-activated rubber powder grafted with SBS.

[0008] As a further aspect of the present invention: the mass ratio of the alkaline washing adhesive powder, the potassium persulfate, the acrylamide and the deionized water is 8-12:0.2-0.3:3-5:100, and the mass ratio of the acrylamide activated adhesive powder, the maleic anhydride and the SBS is 7-9:1:7-9.

[0009] As a further aspect of the present invention, the method for preparing the toughened recycled polyethylene includes the following steps: Partially recycled high-density polyethylene, EPDM rubber, styrene-butadiene rubber and xylene solution were mixed and heated, crosslinking agent and polymerization inhibitor were added, and then benzoyl peroxide was added to react and obtain toughening modifier. The toughening modifier and the remaining recycled high-density polyethylene are added to a twin-screw extruder for melt blending, extruded into thin strips and cut into granules, and dried to obtain toughened recycled polyethylene.

[0010] As a further aspect of the present invention: the mass ratio of the recycled high-density polyethylene, the EPDM rubber, and the styrene-butadiene rubber is 100:24-36:6-9.

[0011] As a further aspect of the present invention: the mass ratio of kaolin to graphene oxide in the kaolin-modified graphene oxide is 3-5:1.

[0012] As a further aspect of the present invention: the coarse aggregate includes one or more of basalt, diabase and granite; the fine aggregate includes one or more of natural sand, manufactured sand and stone chips; the mineral powder includes one or more of lime powder, hydrated lime and cement; and the silane coupling agent is one or a mixture of two of γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0013] A method for preparing coal liquefaction bitumen mixture as described in any one of the above claims, comprising at least the following preparation steps: The base asphalt is heated and then mixed with coal direct liquefaction residue. Then, a silane coupling agent is added and mixed to obtain a composite binder. Acrylamide-activated adhesive powder grafted with SBS and toughened recycled polyethylene were added to the composite binder, heated and sheared at high speed, and then kaolin-modified graphene oxide was added for further dispersion to obtain the functionalized binder. After mixing and preheating coarse aggregate, fine aggregate, and mineral powder, functionalized binder is added, and the mixture is stirred and discharged to obtain coal liquefaction bitumen mixture.

[0014] The beneficial effects of this invention are: The coal liquefaction bitumen mixture prepared by this invention comprises aggregates, mineral powder, base bitumen, coal direct liquefaction residue, toughened recycled polyethylene, acrylamide-activated rubber powder grafted SBS, kaolin-modified graphene oxide, and a silane coupling agent. The coal direct liquefaction residue and kaolin-modified graphene oxide constitute a strong rigid nanoframework, improving the coal liquefaction bitumen mixture's resistance to plastic deformation at high temperatures. The toughened recycled polyethylene and acrylamide-activated rubber powder grafted SBS form an interpenetrating polymer network, providing significant elastic recovery and flexibility, offsetting the brittleness of the coal direct liquefaction residue, and making the mixture less prone to cracking at low temperatures. The silane coupling agent enhances the aggregate-bitumen interface strength, forming a chemically bonded, strong interface between the aggregate and bitumen, improving water damage resistance and durability. The coal liquefaction asphalt mixture provided by this invention transforms coal chemical solid waste, waste plastics and waste tires into high-performance road surface materials, realizing high-value-added resource utilization, and is suitable for extremely harsh occasions such as heavy traffic, high temperature areas, long longitudinal slopes and airport runways.

[0015] This invention employs an alkaline washing and acrylamide activation method to composite the rubber powder. Based on free radical polymerization, the acrylamide-activated rubber powder is grafted with SBS to form acrylamide-activated rubber powder grafted with SBS. The SBS segments swell in the asphalt to form a three-dimensional elastic network, providing excellent elastic recovery. The grafted rubber powder particles act as a flexible dispersed phase, effectively absorbing and dispersing stress. One end of the acrylamide-activated rubber powder grafted with SBS is chemically anchored to the rubber powder surface, while the other end is compatible with the asphalt through SBS, completely solving the problem of poor compatibility between the rubber powder and coal direct liquefaction residue, preventing phase separation and performance degradation. This invention also uses EPDM rubber and styrene-butadiene rubber to toughen recycled polyethylene, forming a ductile polymer phase in the asphalt that interpenetrates with the SBS network, further consuming and dispersing stress energy, providing toughness at low temperatures, and improving low-temperature crack resistance.

[0016] In this invention, kaolin modified with a silane coupling agent opens and attaches to the layers of graphene oxide through electrostatic interactions, forming kaolin-modified graphene oxide with a well-defined intercalation structure. This intercalation structure effectively prevents the stacking and aggregation of the kaolin-modified graphene oxide layers due to intermolecular forces, allowing the graphene oxide to form an invisible "nanoskeleton" in asphalt. This significantly restricts the thermal movement of asphalt molecules, resulting in a significant strengthening and barrier effect. Furthermore, the silane coupling agent transforms traditional physical adsorption into chemical bonding, connecting aggregates and asphalt, and synergistically with the uniformly dispersed graphene oxide layers to effectively slow down the permeation rate of moisture and oxygen in the asphalt film, thus reducing aging. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1: The preparation method of SBS grafted onto acrylamide-activated adhesive powder includes the following steps: The adhesive powder was stirred and soaked in a 5wt% NaOH solution for 30 minutes, washed with deionized water until neutral, and dried in an oven at 60℃ to obtain alkaline-washed adhesive powder. Alkali-washed adhesive powder, potassium persulfate, and acrylamide were placed in a beaker, and deionized water was added to prepare a mixed solution at a mass ratio of 50:1.25:20:500. The solution was magnetically stirred at 65°C for 4 hours. After the reaction was completed, the mixture was washed three times with a large amount of deionized water to remove unreacted acrylamide. The solution was then filtered and dried in a 60°C oven to constant weight to obtain acrylamide-activated adhesive powder. Add 8g of the above acrylamide activated adhesive powder, 1g of maleic anhydride and 8g of SBS to 120mL of cyclohexane. Under high temperature nitrogen atmosphere, add benzoyl peroxide as an initiator. After the reaction is complete, remove excess cyclohexane solvent by vacuum distillation, and then dry in an oven at 60℃ to constant weight to obtain acrylamide activated adhesive powder grafted with SBS.

[0019] Example 2: The preparation method of toughened recycled polyethylene includes the following steps: 30g of recycled high-density polyethylene, 30g of EPDM rubber (3720 / P) and 7g of styrene-butadiene rubber (796) were added to xylene solvent and slowly heated to 125℃. The temperature was kept constant, and 1g of crosslinking agent maleic acid and 1.27g of polymerization inhibitor dimethyl sulfoxide were added. Then benzoyl peroxide was added dropwise. After the reaction was completed, the product was washed and dried to obtain the toughening modifier. The toughening modifier prepared above was added to the remaining 80g of recycled high-density polyethylene in a twin-screw extruder for melt blending, extruded into thin strips and cut into granules, and dried to obtain toughened recycled polyethylene.

[0020] Example 3: The preparation method of toughened recycled polyethylene includes the following steps: 20g of recycled high-density polyethylene, 32g of EPDM rubber (3720 / P) and 8g of styrene-butadiene rubber (796) were added to xylene solvent and slowly heated to 125℃. The temperature was kept constant, and 0.8g of crosslinking agent maleic acid and 1.14g of polymerization inhibitor dimethyl sulfoxide were added. Then benzoyl peroxide was added dropwise. After the reaction was completed, the product was washed and dried to obtain the toughening modifier. The toughening modifier prepared above was added to the remaining 80g of recycled high-density polyethylene in a twin-screw extruder for melt blending, extruded into thin strips and cut into granules, and dried to obtain toughened recycled polyethylene.

[0021] Example 4: The preparation method of kaolin-modified graphene oxide includes the following steps: First, 5g of kaolin was dispersed in 100ml of ethanol and 400ml of deionized water and sonicated for 1h to obtain a kaolin suspension. 2wt% of silane coupling agent KH-550 was hydrolyzed in 50ml of deionized water for 30min. Then, the kaolin suspension and the hydrolysate of the silane coupling agent were poured into a three-necked flask and reacted at 95℃ for 30min. After the temperature dropped to 80℃, a suspension containing 1.25g of graphene oxide was added to the three-necked flask and reacted for 8h. After the reaction was completed, the mixture was washed alternately with deionized water and ethanol, filtered, and dried to obtain kaolin-modified graphene oxide.

[0022] Example 5: A method for preparing a coal liquefaction asphalt mixture includes the following steps: 2.5 parts by weight of base asphalt (70#) were heated to 175℃, and then 2.5 parts by weight of coal direct liquefaction residue with a particle size of 0.1-0.5mm were added and stirred for 20 minutes to make it evenly mixed. Then 0.3 parts by weight of silane coupling agent KH-550 were added and the mixture was sheared at 6000rpm for 35 minutes to obtain composite binder. One part by mass of the acrylamide-activated adhesive powder grafted with SBS prepared in Example 1 and 0.5 parts by mass of the toughened recycled polyethylene prepared in Example 2 were added to the above composite binder. The temperature was kept at 175°C and the mixture was sheared at a high speed of 6000 rpm for 50 minutes. Then, 0.1 parts by mass of the kaolin-modified graphene oxide prepared in Example 4 were added and the mixture was dispersed for another 30 minutes to obtain the functionalized binder. Mix 55 parts by weight of coarse aggregate (basalt), 36 parts by weight of fine aggregate (limestone manufactured sand), and 6 parts by weight of mineral powder (limestone mineral powder). The coarse aggregate, fine aggregate, and mineral powder are all of type AC-13 gradation. Preheat the mixture at 195℃ for 20 minutes, then dry mix for 15-20 seconds before adding the functionalized binder. Wet mix for 90 seconds until the mixture is uniform and consistent. Discharge the mixture to obtain coal liquefaction asphalt mixture.

[0023] Example 6 A method for preparing a coal liquefaction asphalt mixture includes the following steps: 3.2 parts by weight of base asphalt (70#) were heated to 175°C and 1.8 parts by weight of coal direct liquefaction residue with a particle size of 0.1-1mm were added and stirred for 20 minutes to make it evenly mixed. Then 0.25 parts by weight of silane coupling agent KH-550 were added and the mixture was sheared at 6000 rpm for 35 minutes to obtain the composite binder. 0.8 parts by weight of the acrylamide-activated adhesive powder grafted with SBS prepared in Example 1 and 0.4 parts by weight of the toughened recycled polyethylene prepared in Example 3 were added to the above composite binder. The temperature was kept at 175°C, and the mixture was sheared at a high speed of 6000 rpm for 50 minutes. Then, 0.06 parts by weight of the kaolin-modified graphene oxide prepared in Example 4 were added and the mixture was dispersed for another 30 minutes to obtain the functionalized binder. Mix 52 parts by weight of coarse aggregate (basalt), 38 parts by weight of fine aggregate (limestone manufactured sand), and 5 parts by weight of mineral powder (limestone mineral powder). The coarse aggregate, fine aggregate, and mineral powder are all of type AC-13 gradation. Preheat the mixture at 195℃ for 20 minutes, then dry mix for 15-20 seconds before adding the functionalized binder. Wet mix for 90 seconds until the mixture is uniform and consistent. Discharge the mixture to obtain coal liquefaction asphalt mixture.

[0024] Example 7 A method for preparing a coal liquefaction asphalt mixture includes the following steps: Heat 3 parts by weight of base asphalt (70#) to 175℃, then add 2 parts by weight of coal direct liquefaction residue with a particle size of 0.1-0.5mm and stir for 20 minutes to make it evenly mixed. Then add 0.2 parts by weight of silane coupling agent KH-550 and shear at 6000rpm for 35 minutes to obtain composite binder. 1.2 parts by weight of the acrylamide-activated adhesive powder grafted with SBS prepared in Example 1 and 0.7 parts by weight of the toughened recycled polyethylene prepared in Example 2 were added to the above composite binder. The temperature was kept at 175°C and the mixture was sheared at a high speed of 6000 rpm for 50 minutes. Then, 0.08 parts by weight of the kaolin-modified graphene oxide prepared in Example 4 were added and the mixture was dispersed for another 30 minutes to obtain the functionalized binder. Mix 58 parts by weight of coarse aggregate (basalt), 32 parts by weight of fine aggregate (limestone manufactured sand), and 5 parts by weight of mineral powder (limestone mineral powder). The coarse aggregate, fine aggregate, and mineral powder are all of type AC-13 gradation. Preheat the mixture at 195℃ for 20 minutes, then dry mix for 15-20 seconds before adding the functionalized binder. Wet mix for 90 seconds until the mixture is uniform and consistent. Discharge the mixture to obtain coal liquefaction asphalt mixture.

[0025] Compared with Example 6, Comparative Example 1 only replaced the kaolin-modified graphene oxide prepared in Example 4 with the unmodified graphene oxide in Example 4 with the same effective content of graphene oxide. The other components and preparation methods were completely the same as those in Example 6.

[0026] Compared with Example 6, Comparative Example 2 only did not add the kaolin-modified graphene oxide prepared in Example 4, while the other components and preparation methods were completely the same as those in Example 6.

[0027] Compared with Example 6, Comparative Example 3 only replaced the SBS grafted onto the acrylamide activated adhesive powder prepared in Example 1 in Example 6 with the unmodified SBS in Example 1. The other components and preparation methods were completely the same as those in Example 6.

[0028] Compared with Example 6, Comparative Example 4 only replaced the toughened recycled polyethylene prepared in Example 3 with recycled high-density polyethylene in Example 3, while the other components and preparation methods were completely the same as those in Example 6.

[0029] Performance testing Penetration: The container containing asphalt mixture was placed in a 25℃ water bath for 90 minutes for testing. The needle was slowly lowered into the penetration tester, and the reading was recorded when the needle stopped. The penetration temperature was controlled at 25℃. Three parallel tests were performed on the same specimen, and the average value was taken. The test results are shown in Table 1. Softening point: The ring and ball method was used. Asphalt mixture was poured into a mold, and a steel ball from a softening point tester was placed in the center of the mold and fixed with a ring frame. Heating was started from 0°C until the ball fell. Two parallel tests were performed on the same sample, with an error not exceeding 2°C. The test results are shown in Table 1. Ductility: The cast mold was placed in a 5℃ water bath for 90 minutes, then placed in a ductility tester for testing. The water temperature was maintained at 5℃, the tensile rate was 1 cm / min, and the reading was recorded when the specimen broke. The same sample was tested in parallel, with each group tested three times and the average value taken. The test results are shown in Table 1. Brookfield viscosity: The rotor sample container was kept at 170℃ for 1.5h and the asphalt mixture was kept at 170℃ for 90min for testing. The reading was taken every 60s and the average value was taken for 3 consecutive readings. The test results are shown in Table 1. Immersion Marshall test: The specimens were divided into two groups, one group without freeze-thaw cycles and the other group underwent freeze-thaw cycles. Each cycle involved freezing at -18℃ for 16 hours, followed by holding at 60℃ for 8 hours. After removal, the specimens were held in a 60℃ water bath for 48 hours, and the stability was measured. The test results are shown in Table 1. Low-temperature beam bending test: The rutted plate was cut into 250mm×35mm×30mm specimens and placed in a -10℃ environment for 4 hours. Then, at 15℃, the load was concentrated on the middle structure of the specimen at a rate of 50mm / min using a UTM until the specimen broke. The test results are shown in Table 1. High-temperature rutting resistance test: Place a 300mm×300mm×50mm rutting plate into an automatic rutting tester, keep it at 60℃ for 5 hours, and continuously walk back and forth with a test wheel for 1 hour, or end the test when the rutting depth is greater than 25mm; the test results are shown in Table 1. Table 1: Statistical Table of Performance Test Data of Coal Liquefied Pitch Mixtures in Examples 5-7 and Comparative Examples 1-4

[0030] As shown in Table 1, the coal liquefaction asphalt mixtures prepared in Examples 5-7 of this invention possess ultra-high modulus and excellent toughness, exhibiting superior low-temperature crack resistance, high-temperature rutting resistance, and water stability, significantly improving service life. In Comparative Example 1, the added graphene oxide was unmodified, and in Comparative Example 2, no kaolin-modified graphene oxide was added. The high-temperature performance of the obtained coal liquefaction asphalt mixtures decreased significantly, and water resistance also decreased. This indicates that kaolin-modified graphene oxide is a key component for improving high-temperature performance. Furthermore, unmodified graphene oxide is prone to agglomeration, weakening the interface reinforcement and barrier effects. In Comparative Example 3, the added SBS was unmodified, resulting in reduced low-temperature performance of the obtained coal liquefaction asphalt mixture. This indicates that the modified SBS has better compatibility with the rubber powder and can significantly improve low-temperature toughness. In Comparative Example 4, the added recycled polyethylene was not toughened, resulting in decreased high-temperature performance of the obtained coal liquefaction asphalt mixture.

[0031] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0032] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A coal liquefaction bitumen mixture, characterized in that, It shall include at least the following parts by weight of raw materials: 50-60 parts by weight of coarse aggregate; 30-40 parts by weight of fine aggregate; 4-8 parts by weight of mineral powder; 2-3.5 parts by weight of matrix asphalt; 1.5-3 parts by weight of coal direct liquefaction residue; 0.3-0.8 parts by weight of toughened recycled polyethylene; 0.5-1.5 parts by weight of acrylamide activated rubber powder grafted with SBS; 0.05-0.15 parts by weight of kaolin-modified graphene oxide; 0.2-0.4 parts by weight of silane coupling agent; The preparation method of SBS grafted onto acrylamide-activated adhesive powder includes the following steps: The adhesive powder was soaked and stirred in sodium hydroxide solution, washed and dried to obtain alkaline washed adhesive powder. The alkaline-washed adhesive powder, potassium persulfate, and acrylamide were added to deionized water, stirred, washed, filtered, and dried to obtain acrylamide-activated adhesive powder. The acrylamide activated rubber powder, maleic anhydride and SBS were added to cyclohexane, and the reaction was carried out under high temperature nitrogen atmosphere with the initiator benzoyl peroxide. The mixture was then distilled under reduced pressure and dried to obtain acrylamide activated rubber powder grafted with SBS. The method for preparing the toughened recycled polyethylene includes the following steps: Partially recycled high-density polyethylene, EPDM rubber, styrene-butadiene rubber and xylene solution were mixed and heated, crosslinking agent and polymerization inhibitor were added, and then benzoyl peroxide was added to react and obtain toughening modifier. The toughening modifier and the remaining recycled high-density polyethylene are added to a twin-screw extruder for melt blending, extruded into thin strips and cut into granules, and dried to obtain toughened recycled polyethylene.

2. The coal liquefaction asphalt mixture according to claim 1, characterized in that, The asphalt-aggregate ratio of the coal liquefaction pitch mixture is 4.5%-5%, the coarse aggregate, the fine aggregate and the mineral powder are selected from AC-13 type or EME-20 type gradation, and the particle size of the coal direct liquefaction residue is 0.1-1mm.

3. The coal liquefaction asphalt mixture according to claim 1, characterized in that, The mass ratio of the alkaline washing adhesive powder, the potassium persulfate, the acrylamide, and the deionized water is 8-12:0.2-0.3:3-5:100, and the mass ratio of the acrylamide activated adhesive powder, the maleic anhydride, and the SBS is 7-9:1:7-9.

4. The coal liquefaction asphalt mixture according to claim 1, characterized in that, The mass ratio of the recycled high-density polyethylene, the EPDM rubber, and the styrene-butadiene rubber is 100:24-36:6-9.

5. The coal liquefaction asphalt mixture according to claim 1, characterized in that, The mass ratio of kaolin to graphene oxide in the kaolin-modified graphene oxide is 3-5:

1.

6. The coal liquefaction asphalt mixture according to claim 1, characterized in that, The coarse aggregate includes one or more of basalt, diabase and granite; the fine aggregate includes one or more of natural sand, manufactured sand and stone chips; the mineral powder includes one or more of lime powder, hydrated lime and cement; and the silane coupling agent is one or a mixture of two of γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

7. A method for preparing coal liquefaction pitch mixture as described in any one of claims 1-6, characterized in that, It includes at least the following preparation steps: The base asphalt is heated and then mixed with coal direct liquefaction residue. Then, a silane coupling agent is added and mixed to obtain a composite binder. Acrylamide-activated adhesive powder grafted with SBS and toughened recycled polyethylene were added to the composite binder, heated and sheared at high speed, and then kaolin-modified graphene oxide was added for further dispersion to obtain the functionalized binder. After mixing and preheating coarse aggregate, fine aggregate, and mineral powder, functionalized binder is added, and the mixture is stirred and discharged to obtain coal liquefaction bitumen mixture.

Citation Information

Patent Citations

  • High-modulus asphalt mixture and preparation method thereof

    CN105884264A

  • Coal liquefaction residue compound asphalt and preparation method thereof

    CN106317920A